The Demography, Health Status and Public Attitude of Owned Dog In Bharatpur Metropolitan City: Canine welfare in nepal - Mahato, Prem Lal; Kandel, Milan; Khanal, Shrijana; Subedi, Deepak; K.C, Bishnu; Wilson, Douglas (International Journal of Applied Sciences and Biotechnology, 2020)
Dog play an important role as companion and guard animal. In Nepal, most dogs are free to roam and only few of household keep the dog as owned-dog. This study was carried out at Bharatpur Metropolitan City, Chitwan where 95 dogs owned families who owned 119 dogs were purposively surveyed with well-structured pretested questionnaire to collect baseline data on owned dog demographics, assess knowledge, attitudes and practices of dog owners concerning dogs. In the study, the sex ratio was found 1:1 in the population. Median age of population was found to be 2.5 years and range from 1 month to 12 year. Respondents showed no any specific preference for keeping dogs i.e. 39.5% for male, 23.5% for female and while 37% does not concern about the sex and most animals were kept for companionship (52.9%). Of those surveyed mixed dogs, of no definable cross, were most common, followed by Japanese Spitz (23.5%) and German shepherd (11.8%). Results show that 92.1% of respondent have knowledge on vaccination schedule while 94% of dog were vaccinated and 82.4% dog were routinely de-wormed. Study findings revealed that majority owner reported the dog were not facing any major problem (84.9%) while some are facing ecto-parasite problem ( 7.5 %) followed by dermatological problem (2.5%), endo-parasite problem (2.4%) and viral disease (1.6%). Among the total population only in 15.1% neutering was done Thus, based on the findings of present study, it is concluded that focus should be given to animal birth control program (ABC) while developing health management strategies. Meanwhile, further study covering wider geography and considering the major risk factors is recommended. Keywords: Animal Birth Control (ABC); Disease; Dog and Vaccination Schedule